(untitled) (Research, Society and Development, 2020)
This study reviews the use of Apocynaceae species for cancer and tumor treatment in the Amazon. Databases and books were searched for ethnobotanical and phytochemical evaluations of the cytotoxic and anticancer activities of Apocynaceae species. The literature reports the use of several Amazonian species, such as Asclepias curassavica, Himatanthus articulates, and Macoubea sprucei, in treating tumors and cancers. Phytochemical studies on A. curassavica and H. articulatus have shown their chemical compositions to be variable, possessing cardenolides, iridoids, flavonoids, steroids, and terpenes. Most of the species have not been subjected to in vitro experiments for anticancer activity, and the evaluated species showed moderate-to-weak responses or were inactive. Other studies have shown that iridoids, flavonoids, and steroids are promising as antitumor treatments. The following action mechanisms have been attributed to iridoids: topoisomerase I-DNA complex stabilization, cellular cytoskeleton alteration, and induction of apoptosis. The activities of flavonoids have been reported to include apoptosis induction in liver tumor cells. Some authors suggest that flavonoids reduce oxidative stress cellular response which reduces mitochondrial dysfunction and cell death. In summary, Apocynaceae species appear to be promising as a source for antitumor agents; however, further studies are required to confirm their antitumor activities and to better elucidate the underlying mechanisms involved.